2023
DOI: 10.1093/jbcr/irad026
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Human Dermal Fibroblasts Exposed to Hydrogen Peroxide by Regulating Autophagy Level and Reactive Oxygen Species Generation

Abstract: Curcumin is getting more and more attention in wound healing and scar prevention because of its wide range of pharmacological effects, such as anti-inflammation, antioxidant and anti-fibrosis. The activity of fibroblasts suffering from oxidative stress is reduced, affecting wound repair. In this study, we investigated whether curcumin treatment (10 μM, 24 h) had protective effects on human dermal fibroblasts (HDFs) exposed to hydrogen peroxide (H2O2, 300 μM, 12 h). We found that curcumin alleviated H2O2-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…25 Our team has recently reported that the cultivation of fibroblasts with curcumin at 10 μmol/L can promote autophagy and defend cells against ROS attack after hydrogen peroxide exposure. 26 More curcumin concentrations and fibroblasts from different phases of wound repair need to be studied to elaborate the effect of curcumin on the oxidant-antioxidant balance of fibroblasts, which determines whether it is applied for wound healing or scar treatment. In addition, high-dose oral curcumin is considered safe for clinical use, which also indicates its poor systemic bioavailability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Our team has recently reported that the cultivation of fibroblasts with curcumin at 10 μmol/L can promote autophagy and defend cells against ROS attack after hydrogen peroxide exposure. 26 More curcumin concentrations and fibroblasts from different phases of wound repair need to be studied to elaborate the effect of curcumin on the oxidant-antioxidant balance of fibroblasts, which determines whether it is applied for wound healing or scar treatment. In addition, high-dose oral curcumin is considered safe for clinical use, which also indicates its poor systemic bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…However, high concentrations of curcumin induce fibroblast apoptosis by increasing the generation of reactive oxygen species (ROS), while low concentrations improve heme oxygenase‐1 activity and protect cells from oxidative injury 25 . Our team has recently reported that the cultivation of fibroblasts with curcumin at 10 μmol/L can promote autophagy and defend cells against ROS attack after hydrogen peroxide exposure 26 . More curcumin concentrations and fibroblasts from different phases of wound repair need to be studied to elaborate the effect of curcumin on the oxidant‐antioxidant balance of fibroblasts, which determines whether it is applied for wound healing or scar treatment.…”
Section: Discussionmentioning
confidence: 99%